PEMBELAJARAN KOOPERATIF BERBANTUAN MEDIA AUDIO VISUAL PADA MATA KULIAH PENDIDIKAN ILMU PENGETAHUAN SOSIAL - Ahmad Hariyadi; Fuadul Matin; Alvinda Putri (Universitas Muria Kudus, 2021)
The purpose of this study is to analyze how students apply cooperative learning techniques in the classroom to find out case studies of the application of these techniques in student social studies education learning.The research method used is qualitative. The main data collection techniques of this study used classroom observation, group interviews and lecturer interviews to help us gain insight into how cooperative learning is applied by lecturers, oral expressions and student attitudes towards small group learning.The results showed that cooperative learning in small groups can improve student socialstudies education learning and ensure the application of cooperative learning techniqueshas negative aspects such as creating noise in the classroom and group conflict if themanagement and planning of the lecturer's learning is not optimal. Based on the resultsobtained, we recommend that colleagues, both lecturers and students, can reduce theproblems that hinder the successful implementation of cooperative learning in theclassroom.